Competition and relationship lending: Friends or foes? - Andrea F. Presbitero; Alberto Zazzaro (Center for Economic Studies and ifo Institute (CESifo), 2010)
Recent empirical findings by Elsas (2005) and Degryse and Ongena (2007) document a U-shaped effect of market concentration on relationship lending which cannot be easily accommodated by the investment and strategic theories of relationship lending. In this paper, we suggest that this non-monotonicity can be explained by looking at the organizational structure of local credit markets. We provide evidence that marginal increases in interbank competition are detrimental to relationship lending in markets where large and out-of-market banks are predominant. On the contrary, where relational-based lending technologies are al-ready widely in use in the market by a large group of small mutual banks, an increase in competition may drive banks to further cultivate their extensive ties with customers.
Keywords: G21; L11; 330; interbank competition; market organizational structure; relationship lending; Kreditgeschäft; Hausbank; Lieferanten-Kunden-Beziehung; Regionalbank; Wettbewerb; Regionaler Finanzmarkt; Marktstruktur; Italien